PRMT5 restricts hepatitis B virus replication through epigenetic repression of covalently closed circular DNA transcription and interference with pregenomic RNA encapsidation. Issue 2 (19th June 2017) - Zhang, Wen; Chen, Jieliang; Wu, Min; Zhang, Xiaonan; Zhang, Min; Yue, Lei; Li, Yaming; Liu, Jiangxia; Li, Baocun; Shen, Fang; Wang, Yang; Bai, Lu; et al.
Abstract : Chronic hepatitis B virus (HBV) infection remains a major health problem worldwide. The covalently closed circular DNA (cccDNA) minichromosome, which serves as the template for the transcription of viral RNAs, plays a key role in viral persistence. While accumulating evidence suggests that cccDNA transcription is regulated by epigenetic machinery, particularly the acetylation of cccDNA‐bound histone 3 (H3) and H4, the potential contributions of histone methylation and related host factors remain obscure. Here, by screening a series of methyltransferases and demethylases, we identified protein arginine methyltransferase 5 (PRMT5) as an effective restrictor of HBV transcription and replication. In cell culture–based models for HBV infection and in liver tissues of patients with chronic HBV infection, we found that symmetric dimethylation of arginine 3 on H4 on cccDNA was a repressive marker of cccDNA transcription and was regulated by PRMT5 depending on its methyltransferase domain. Moreover, PRMT5‐triggered symmetric dimethylation of arginine 3 on H4 on the cccDNA minichromosome involved an interaction with the HBV core protein and the Brg1‐based human SWI/SNF chromatin remodeler, which resulted in down‐regulation of the binding of RNA polymerase II to cccDNA. In addition to the inhibitory effect on cccDNA transcription, PRMT5 inhibited HBV core particle DNA production independently of its methyltransferase activity. Further study revealed that PRMT5 interfered with pregenomic RNA encapsidation by preventing its interaction with viral polymerase protein through binding to the reverse transcriptase–ribonuclease H region of polymerase, which is crucial for the polymerase–pregenomic RNA interaction. Conclusion : PRMT5 restricts HBV replication through a two‐part mechanism including epigenetic suppression of cccDNA transcription and interference with pregenomic RNA encapsidation; these findings improve the understanding of epigenetic regulation of HBV transcription and host–HBV interaction, thus providing new insights into targeted therapeutic intervention. (Hepatology 2017;66:398–415).